The cytoprotective effect of different doses of Sildenafil on indomethacin-induced gastric mucosal damage in rats: - Matloub, Samir Y. N.; Manna, Mohammed J. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Sildenafil, a selective phosphodiesterase -5 (PDE-5) inhibitor increases cyclic guanosine monophosphate (cGMP) and amplifies many biological actions of nitric oxide (NO) which is an important mediator of gastric mucosal defense ; was evaluated in this study using different doses for its cytoprotective effect on gastric mucosal damage induced by indomethacin . We also evaluated the effect of this drug on NO production, Prostaglandin E2 (PGE2) synthesis, Myeloperoxidase (MPO) activity, and Interlukin-4 (IL-4) expression. Methods: The study was performed between April and July 2008 in the Department of Pharmacology / College of Medicine /Baghdad University .It was conducted on 80 adult male albino rats, divided into 8 groups, the first served as a control received the vehicle, the second received indomethacin orally of 60mg/kg .The third and fourth groups were pretreated 30 minutes prior indomethacin with oral sildenafil 10 and 20mg/kg respectively. The other groups were pretreated 30 minutes prior to sildenafil (10and20mg/kg) with intraperitoneal NG-L-Arginine Methyl Ester (L-NAME) 20mg/kg with or without L-Arginine. The rats were then sacrificed after 4 hours and their stomachs were isolated and submitted to macroscopical assessment and for the measurement of the gastric PGE2, MPO, and IL-4. Results: Sildenafil (10 and 20 mg/kg) pretreatment resulted in a significant (p<0.01) decrease in the gastric damage score. The MPO activity was significantly (p<0.01) decreased, while the level of IL-4 was significantly (p<0.01) increased. On the other hand PGE2 level was not changed. L-NAME given 30 min before 10 and 20 mg/kg sildenafil, significantly (p<0.01) abolished the protective effects of sildenafil and also reversed the effects of sildenafil on MPO activity and IL-4 levels. On the other hand addition of L-Arginine resulted in the restoration of the protective effects of sildenafil which was also reflected on the gastric damage score, MPO activity and IL-4 levels. Conclusions: The results demonstrate that the injurious effect of indomethacin can be reduced or ameliorated by sildenafil pretreatment, and that the protective effect of sildenafil against indomethacin was through an NO dependent pathway.